2018
DOI: 10.1021/acs.jpclett.8b00616
|View full text |Cite
|
Sign up to set email alerts
|

A New Anisotropic Dirac Cone Material: A B2S Honeycomb Monolayer

Abstract: Different from the isotropic Dirac cones existing in other two-dimensional (2D) materials, anisotropic Dirac cones have the merit of anisotropic carrier mobility for applications in direction-dependent quantum devices. Motivated by the recent experimental finding of an anisotropic Dirac cone in borophene, here we report a new 2D anisotropic Dirac cone material, BS monolayer, identified by using a global structure search method and first-principles calculation combined with a tight-binding model. The BS monolay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 62 publications
6
84
0
Order By: Relevance
“…As very recently reported [4], the most energetically stable structure of B 2 S monolayer predicted by using global structure search method and first principles calculation combined with tight-binding model, is shown in Fig.1 from which we can see that the planar 2D structure consists of honeycomb lattices, similar to graphene. This honeycomb structure is a global minimum in the space of all possible 2D arrangements of B 2 S in which each hexagonal ring is distorted with the bond angles ranging from 114Å to 123Å, because B and S atoms have different covalent radii and electronegativities [4,5].…”
Section: B Armchair B2s Nanoribbonssupporting
confidence: 66%
See 1 more Smart Citation
“…As very recently reported [4], the most energetically stable structure of B 2 S monolayer predicted by using global structure search method and first principles calculation combined with tight-binding model, is shown in Fig.1 from which we can see that the planar 2D structure consists of honeycomb lattices, similar to graphene. This honeycomb structure is a global minimum in the space of all possible 2D arrangements of B 2 S in which each hexagonal ring is distorted with the bond angles ranging from 114Å to 123Å, because B and S atoms have different covalent radii and electronegativities [4,5].…”
Section: B Armchair B2s Nanoribbonssupporting
confidence: 66%
“…The geometrical structure of the pristine armchair edge B 2 S nanoribbon, lying in the xy plane, is depicted in Fig.1 (d). As shown in this figure, each hexagon consists of four B atoms and two S atoms, with an orthogonal primitive cell with a space group of P BAM and a point group D 2 h. As shown in Fig.1, the bonding length between two adjacent B atoms (B-B bonds) was calculated to be 1.62Å, from the relaxed structure whereas the distances between B and S atoms (B-S bonds), are all of the same length 1.82Å [4]. The black balls correspond to the boron atoms (B) and the white ones correspond to the sulfur atom (S).…”
Section: B Armchair B2s Nanoribbonsmentioning
confidence: 99%
“…The geometry structure of a monolayer zigzag nanoribbon of B 2 S, laid in the xy plane, is depicted in Fig.1. As shown in this figure, each hexagon consists of four B atoms and two S atoms, with an orthogonal primitive cell with a space group of P BAM and a point group D 2 h. In this structure, there are two kinds of bonds with 1.62Åand 1.82Åbond lengths for B-B and B-S connections, respectively [38].…”
Section: Theory and Modelmentioning
confidence: 99%
“…To verify the role of strain in the magnetic exchange interaction, the understanding of changes in the band structure and bandgap transformation is crucial. For B 2 S monolayer, it is shown that the bands near the Fermi level are originated from the p z orbitals [38]. A nearest-neighbor effective tight-binding Hamiltonian, in the basis of p z orbitals and in the second quantized representation has recently been modeled [38] and is given by…”
Section: Theory and Modelmentioning
confidence: 99%
See 1 more Smart Citation